2020
DOI: 10.1111/acer.14302
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Ethanol Seeking and Licking Microstructure of Enhanced Ethanol Self‐Administration in Ethanol‐Dependent Mice

Abstract: Background: A significant component of ethanol (EtOH) dependence is the disruption to decision-making processes. Prior work has shown EtOH dependence biases habitual seeking of EtOH and disrupts neural mechanisms supporting decision-making. This has contributed to the hypothesis that habitual EtOH seeking in EtOH dependence may promote excessive habitual or compulsive EtOH consumption. However, decision-making and behavioral processes underlying seeking and consummatory behaviors differ. Here, we examine the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 55 publications
(78 reference statements)
3
28
2
Order By: Relevance
“…In contrast to recent findings reporting significant escalation in ethanol consummatory behavior (i.e., licking) following CIE (Renteria et al, 2020), we did not observe an escalation in licking following CIE (data not shown). A mixed‐model ANOVA indicated no significant CIE × session interaction, F (12, 176) = 0.9448, p = 0.5037.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to recent findings reporting significant escalation in ethanol consummatory behavior (i.e., licking) following CIE (Renteria et al, 2020), we did not observe an escalation in licking following CIE (data not shown). A mixed‐model ANOVA indicated no significant CIE × session interaction, F (12, 176) = 0.9448, p = 0.5037.…”
Section: Resultscontrasting
confidence: 99%
“…Importantly, this indicates that the Air control mice may have developed contingency‐insensitive habits following repeated training on these schedules, but that CIE facilitated the transition from actions to habits. This interpretation is complementary to findings from others that CIE induces outcome devaluation‐insensitive ethanol‐seeking behaviors (Renteria et al, 2020), indicating that a history of chronic ethanol exposure may facilitate habitual behaviors that are both outcome and contingency‐insensitive. This is further consistent with reports that ethanol‐seeking habits develop more rapidly than sucrose‐seeking habits (Dickinson et al, 2002).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations